AIRMESS – Academy of International Regenerative Medicine & Surgery Societies: recommendations in the use of platelet-rich plasma (PRP), autologous stem cell-based therapy (ASC-BT) in androgenetic alopecia and wound healing. (2nd November 2021) - Gentile, Pietro; Alves, Rubina; Cole, John P.; Andjelkov, Katarina; Van Helmelryck, Thierry; Fernandez, Jonathan; Trivisonno, Angelo; Guillaume, Lemierre; Verpaele, Alexis; Tonnard, Patrick; Magalon, Jeremy; Magalon, Guy; et al.
ABSTRACT: Introduction: Many investigations showed that platelet-rich plasma (PRP), human follicles stem cells (HFSCs), and adipose-derived stem cells (ASCs), considered autologous stem cell-based therapy (ASC-BT), are effective for hair regrowth (HR) in patients affected by androgenetic alopecia and for wound healing (WH). The aim of this article is to analyze the in vitro and in vivo impact of different PRP, HFSCs, and ASCs preparation methods on HR and in WH. Areas Covered: The analyzed data intended to clarify the molecular mechanism in which PRP, HFSCs, and ASCs are involved, the clinical use and related indications, fully respecting the European rules. Comparative studies between different systems of PRP, HFSCs, and ASCs preparation revealed differences in terms of HR and WH. Expert Opinion: Despite a lack of standardized protocols, there is convincing evidence with objective measurement modalities that display positive outcomes of ASC-BT in HR and WH.